Front line surgery a practical approach - Martin, Matthew; Beekley, Alec.; SpringerLink (Online service). (New York Springer, 2011)
Both editors are active duty officers and surgeons in the U.S. Army. Dr. Martin is a fellowship trained trauma surgeon who is currently the Trauma Medical Director at Madigan Army Medical Center. He has served as the Chief of Surgery with the 47th Combat Support Hospital (CSH) in Tikrit, Iraq in 2005 to 2006, and most recently as the Chief of Trauma and General Surgery with the 28th CSH in Baghdad, Iraq in 2007 to 2008. He has published multiple peer-reviewed journal articles and surgical chapters. He presented his latest work analyzing trauma-related deaths in the current war and strategies.
Prehospital and enroute care -- Combat triage and mass casualty management -- Initial management priorities: beyond ABCDE -- Damage control resuscitation -- To operate or image?: pulling the trigger -- Ultrasound in combat trauma -- The bowel: contamination, colostomies, and combat surgery -- Liver and spleen injury management in combat (old school) -- Pancreatic and duodenal injuries (sleep when you can ...) -- Operative management of renal injuries -- Major abdominal vascular trauma -- To close or not to close: managing the open abdomen -- Choice of thoracic incision -- Lung injuries in combat -- Diagnosis and management of penetrating cardiac injury -- Thoracic vascular injuries: operative management in "enemy territory" -- Chest wall and diaphragm injury -- Soft tissue wounds and fasciotomies -- Extremity injuries and open fractures -- Mangled extremities and amputations -- Peripheral vascular injuries -- The neck -- Geritourinary injuries (excluding kidney) -- Neurosurgery for dummies -- Spine injuries -- Face, eye, and ear injuries -- Burn care in the field hospital -- The pediatric patient in wartime -- The combat ICU team -- Postoperative resuscitation -- Monitoring -- Ventilator management: a practical approach to respiratory failure in combat casualties -- Practical approach to combat-related infections and antibiotics -- Stabilization and transfer from the far forward environment -- Humanitarian and local national care -- Expectant and end of life care in a combat zone.
Electronic reproduction.
Keywords: Surgery, Military; Wounds and injuries -- Surgery; Military Medicine -- methods; Military Personnel; Surgical Procedures, Operative -- methods; Wounds and Injuries -- surgery; Electronic books